Genetic differentiation of Diplodus sargus (Pisces: Sparidae) populations in the south-west Mediterranean - González-Wangüemert, Mercedes; Pérez-Ruzafa, Á.; Marcos, C.; García-Charton, J. A. (Linnean Society of London, 2004)
Allozyme analysis of tissue samples of 1249 white sea bream Diplodus sargus from five localities of the south-west Mediterranean revealed a high degree of genetic polymorphism. The observed heterozygosity ranged from 0.4182 (Cape of Palos) to 0.3138 (Tabarca). Several populations were characterized by unique alleles. Examination of the spatial structure was performed using Nei’s distances and F-statistics, and indicated genetic differences between groups. One group, which clustered Tabarca and Guardamar, could be explained by the small geographical distance between them. Mazarrón and Cape of Palos samples showed genetic divergence from other samples (Guardamar, Tabarca and Águilas) and this difference may be as a result of local current systems and larval dispersal. info:eu-repo/semantics/publishedVersion